The impacts of demand response participation in capacity markets - Muireann Á. Lynch; Sheila Nolan; Mel T. Devine; Mark O'Malley (The Economic and Social Research Institute (ESRI), 2018)
Demand Response (DR) is capable of reducing the need for generation capacity investments in order to ensure system security. We utilise this fact to devise a novel methodology for estimating a load-shifting DR resource's capacity contribution and therefore determining DR's potential for participation in capacity markets. DR primarily affects the equilibrium outcome through the energy market, however DR also reduces prices and consumer costs through its capacity market contribution when there is a high level of variable renewable generation and initial undercapacity. As wind levels increase, so do capacity prices as generators seek higher capacity prices to offset depressed energy prices. However, we find that DR's participation in the capacity market can combat these increased capacity prices. These results suggest that DR participation in capacity markets can mitigate some of the market challenges of renewable integration.
Keywords: 330; Demand Response; Load-Shifting; Markets; Reserve; Capacity